THE SIGNIFICANCE OF USING HIGHER ORDER POLYNOMIALS TO DESCRIBE THE (O-C) DIAGRAMS OE ECLIPSING BINARIES - Rovithis-Livaniou, H.; Rovithis, P.; Kalimeris, A. (Одеські астрономічні публікації, 2017)
The principal aim of the present study is to underline the significance of using higher order polynomials to describe the (O-C) diagrams of eclipsing binary systems.